Sunday, March 20, 2022

March Calculus Madness Sweet Sixteen - Day 5: x^n ∙ √(1 + x)

 ------------


Welcome to March Calculus Madness!


------------


d/dx x^n ∙ √(1 + x)


Here we can make use the multiplication rule:

d/dx f(x) ∙ g(x) = f(x) ∙ g'(x) + f'(x) ∙ g(x)


In this case:

f(x) = x^n

g(x) = √(1 + x) = (1 + x)^(1/2)


Then:

f'(x) = n ∙ x^(n-1)

g'(x) = 1/2 ∙ (1 + x)^(-1/2)


And: 

d/dx x^n ∙ √(1 + x) 

= x^n ∙ 1/2 ∙ (1 + x)^(-1/2) + n ∙ x^(n-1) ∙ (1 + x)^(1/2)


For indefinite integrals, I will do two specific cases of n.


∫ x ∙ √(1 + x) dx   (n = 1)


Using integration by parts:


u = x,  dv = (1 + x)^(1/2) dx

du = dx,  v = 2/3 ∙ (1+x)^(3/2)



∫ x ∙ √(1 + x) dx

= 2/3 ∙ (1+x)^(3/2) ∙ x - ∫ (1 + x)^(1/2) dx

= 2/3 ∙ (1+x)^(3/2) ∙ x - 2/3 ∙ (1 + x)^(3/2) + C

= 2/3 ∙ (1 + x)^(3/2) ∙ (x - 1) + C


∫ x^2 ∙ √(1 + x) dx   (n = 2)


Let z = (1 + x)^(1/2)

dz = 1/2 ∙ (1+ x)^(-1/2) dx

2 ∙ (1+x)^(1/2) dz = dx

2 ∙ z  dz = dx


z^2 = 1 + x

z^2 - 1 = x

z^4 - 2 ∙ z^2 + 1 = x^2


∫ x^2 ∙ √(1 + x) dx   

= ∫ (z^4 - 2 ∙ z^2 + 1) ∙ z ∙ 2 ∙ z dz

= ∫ (z^4 - 2 ∙ z^2 + 1) ∙ 2 ∙ z^2 dz

= ∫ 2 ∙ z^6 - 4 ∙ z^4 + 2 ∙ z^2 dz

= 2/7 ∙ z^7 - 4/5 ∙ z^5 + 2/3 ∙ z^3 + C

= 2/7 ∙ (1 + x)^(7/2) - 4/5 ∙ (1 + x)^(5/2) + 2/3 ∙ (1 + x)^(3/2) + C

(z = (1 + x)^(1/2))


Eddie


All original content copyright, © 2011-2022.  Edward Shore.   Unauthorized use and/or unauthorized distribution for commercial purposes without express and written permission from the author is strictly prohibited.  This blog entry may be distributed for noncommercial purposes, provided that full credit is given to the author. 


Casio fx-991 CW: Solving Linear Systems of Complex Numbers

Casio fx-991 CW: Solving Linear Systems of Complex Numbers Introduction The fx-991 CW is a capable calculator. It even handles comple...